DOMESTIC SOLID WASTE MANAGEMENT SYSTEM PLANNING IN CIKERUH VILLAGE, JATINANGOR SUB-DISTRICT - Nasrullah Ahmad, Muhammad
Cikeruh Village is one of the most populated villages in Jatinangor Subdistrict, has 6 tons of waste generation every day. The high value of waste generation is not managed properly, so that illegal dumping is often done by the community. Disposal of illegal dumping on vacant lands, roadsides, and river banks is increasingly out of control, thus adversely affecting environmental conditions. Planning of waste management and service systems that cover social and technical aspects such as institutional formation, closure of illegal dumping sites, collection service plans, and the design of the 3R transfer station is a solution to create healthy and advanced environment so that the quality of life of the village communityin Cikeruh Village improving. In planning the system, surveys, identification, data collection and evaluation are used as the basis for design. Development of solid waste management with a 10 years service is expected to reach 95% of solid waste services and increase community participation to participate in managing waste with 15% reduction at the source. Waste collection service is planned by dividing into 6 service zones to facilitate the service capacity of each collection fleets which served by 2 motorcycles, 1 car and 6 carts The capacity of system planned to serve 8 tons / day with composition of organic waste by 51% and inorganic by 32% with 46 % of organic waste contain of food leftovers it becomes potential to produce energy using a waste-to-energy concept.. Handling of waste in 3R transfer station includes processing organic waste and anorganic waste handling. The organic waste is processed using anaerobic digester and aerated windrow technology. The anorganic waste is disaggregated and distributed to recyclers. The processing of organic waste is processed using of anaerobic digester and aerated windrow technology. Solid waste management system planning and 3R transfer station in Cikeruh Village are expected to provide a change in community lifestyle so as to create a healthy and clean environment for the community